An exploratory bibliometric analysis of the literature on the age of information-aware unmanned aerial vehicles aided communication - Bukar, Umar Ali; Sayeed, Md Shohel; Abdul Razak, Siti Fatimah; Yogarayan, Sumendra; Amodu, Oluwatosin Ahmed (Informatica, 2023)
Real-time status updates require more frequent updates with fresh information. This study investigates the applications and research potential of unmanned aerial vehicles (UAV) for achieving information freshness in time-critical applications to emphasize important aspects of this subject based on a thorough statistical analysis of current research trends. Particularly using the Scopus database, a bibliometric analysis is conducted on 122 articles written in English and published between 2018 and 2023. This analysis provides a knowledge map of past research on this subject and the journey so far, especially concerning major subjects, patterns of citations, publication activities, and the state of cooperation among contributors throughout the UAV-information freshness research history. According to the findings, applying various methods, such as deep reinforcement learning and optimization algorithms, has been evident. In contrast, energy efficiency and harvesting, trajectory planning and design, and scheduling are issues attracting researchers' interest. The study offers implications for policy and practices.